2016
DOI: 10.11648/j.edu.20160503.11
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Awareness and Utilization of the Essential Electronic Agricultural Library for Teaching and Research: A Study of Academic Staff in the University of Calabar, Nigeria

Abstract: This study reports on a survey conducted to explore the awareness and extent of utilization of The Essential Electronic Agricultural Library (TEEAL) database resources by academic staff at the faculty of Agriculture, University of Calabar, Nigeria. Structured Questionnaire was designed and used for data collection. Eighty copies of the questionnaire were randomly distributed to respondents in their offices; 60 copies of these were retrieved and used for data analysis (with 75.0% response rate). The findings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These findings were not surprising, especially as the interviewed library directors noted that they had tried to implement common trends. Several previous studies had reported the availability of e-resources (Edem and Egbe, 2016;Mawere and Sai, 2018;Mwantimwa and Elia, 2017;Tella et al, 2018), IRs (Di Salvo et al, 2015Kakai et al, 2018;Namaganda, 2017;Shajitha and Majeed, 2018), remote access (Blansit, 2007;De Sarkar, 2015), social media (Akeriwa et al, 2015;Okoroma, 2018;Trucks, 2019) and ILMS (Komolafe-Opadeji and Ojo, 2019) in university libraries.…”
Section: Implemented Digital Transformation In University Libraries I...mentioning
confidence: 99%
“…These findings were not surprising, especially as the interviewed library directors noted that they had tried to implement common trends. Several previous studies had reported the availability of e-resources (Edem and Egbe, 2016;Mawere and Sai, 2018;Mwantimwa and Elia, 2017;Tella et al, 2018), IRs (Di Salvo et al, 2015Kakai et al, 2018;Namaganda, 2017;Shajitha and Majeed, 2018), remote access (Blansit, 2007;De Sarkar, 2015), social media (Akeriwa et al, 2015;Okoroma, 2018;Trucks, 2019) and ILMS (Komolafe-Opadeji and Ojo, 2019) in university libraries.…”
Section: Implemented Digital Transformation In University Libraries I...mentioning
confidence: 99%
“…[24] [25] believes that e-resources are the main gateway that provides users with the information needed to conduct investigations in various fields. University e-resources are the main part of the library websites and have become a vital academic resource that supports teaching, learning, and research activities [26]. e-Resources play an essential role as a source of information in providing quick and easy service to readers [13].…”
Section: Introductionmentioning
confidence: 99%